Is there an information age in the whole developmental stages of the substance civilization of human society? - Bangwei, Zhang (Advances in Social Sciences Research Journal, 2019)
The "information age" and "information society" that have emerged in recent years and that have been clamored and overhyped by some people are not real existed. The entire historical facts of human society have proved that information and its communication and dissemination have existed since the advent of human beings. With the advancement of substance civilization, the highly developed information technology and means of communication are always accompanied, never left and interrupted. The six-stage theory proposed by the author for the development of material civilization in human society has theoretically ruled out the standard of information as the dividing stage of development of material civilization. Therefore either from the whole history facts or from the theoretical analysis there is no anyplace for the information age acting as a certain stage of the historical process of human social development.